Preparation process of high-thermal-conductivity polyimide film
By adding modified carbon nanotubes to the polyimide film, the problem of insufficient thermal conductivity and antistatic properties of the polyimide film is solved, and the combination of high thermal conductivity and excellent mechanical properties is achieved, which is suitable for the thermal management and mechanical performance requirements of modern electronic equipment.
Patent Information
- Application Number
- CN202510420900.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyimide film has low thermal conductivity and insufficient antistatic properties, making it difficult to meet the demands of modern electronic equipment for high thermal conductivity and excellent mechanical properties.
By adding homemade modified carbon nanotubes to the polyimide film, the modified carbon nanotubes improve their compatibility with polyimide by grafting the organic molecular chains, and a highly thermally conductive polyimide film is prepared by sonication, vacuum defoaming, casting film formation, thermal cyclization and bidirectional thermal drafting treatment.
It significantly improves the thermal conductivity and antistatic properties of polyimide films, while enhancing its flexibility and mechanical properties, meeting the demands of modern electronic equipment for high thermal conductivity and excellent mechanical properties.
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a preparation process of a high thermal conductivity polyimide film. Background Art
[0002] With the rapid development of modern science and technology, the demand for electronic devices in terms of functional diversification, performance improvement and miniaturization is increasing. This trend has put forward higher requirements on materials science, especially in the field of thermal management. Efficient thermal management is essential to extend the service life of electronic devices and improve their stability and reliability. However, although traditional thermal conductive materials such as metals and ceramics have high thermal conductivity, they often have disadvantages such as heavy weight, high processing difficulty or poor flexibility, which makes it difficult to meet the needs of modern electronic equipment for lightweight and flexibility. Therefore, the development of new materials with both high thermal conductivity and excellent mechanical properties has become one of the key directions of current research.
[0003] Polyimide (PI) refers to a class of polymers containing imide rings on the main chain. As a high-performance polymer material, polyimide is widely used in aerospace, microelectronics, flexible display and other fields due to its excellent thermal stability, chemical stability, mechanical properties and good electrical insulation. However, the thermal conductivity of ordinary polyimide films is low (usually less than 0.2 W / m·K), which limits its application in efficient thermal management. In order to overcome this shortcoming, researchers have tried to improve the thermal conductivity of polyimide materials through various methods in recent years, such as introducing high thermal conductivity fillers, optimizing molecular structure design and improving preparation processes.
[0004] At present, the research on high thermal conductivity polyimide film mainly focuses on the following aspects: First, the strategy of filling composite materials, that is, adding high thermal conductivity fillers (such as graphene, carbon nanotubes, boron nitride, etc.) into the polyimide matrix to form a thermal conductive path. This method can significantly improve the thermal conductivity of the material, but it also faces some challenges, such as how to achieve uniform dispersion of fillers, avoid the increase in thermal resistance caused by interface defects, and control the overall mechanical properties of the material from decreasing due to excessive addition of fillers. In addition, polyimide has high strength and modulus, but high brittleness and lack of sufficient toughness. It is prone to brittle cracking after impact or repeated bending. Not only that, polyimide is used in electronic components. Due to its insufficient antistatic performance, static electricity accumulates on electronic components, which will cause dust accumulation on the components. In view of the above problems, the present invention proposes a preparation process of high thermal conductivity polyimide film to meet the higher requirements in the field of polyimide film technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a preparation process of a high thermal conductive polyimide film.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A process for preparing a high thermal conductive polyimide film comprises the following steps: A1. Add aromatic dianhydride, aromatic diamine and N,N-dimethylformamide into a reaction kettle, introduce nitrogen as a protective gas, set the temperature to 20-30°C, stir and react for 20-30 minutes to obtain a polyamic acid solution; A2. The polyamic acid solution obtained in step A1 is ultrasonically treated with modified carbon nanotubes and a dispersant for 10-30 minutes, and then vacuum defoamed, cast into a film, and then thermally cyclized and bidirectionally thermally stretched, and rolled up to obtain a high thermal conductive polyimide film.
[0007] Furthermore, the raw materials are calculated in parts by weight as follows: 51-63 parts of aromatic dianhydride, 43-55 parts of aromatic diamine, 110-160 parts of N,N-dimethylformamide, 12-24 parts of modified carbon nanotubes, and 2-4 parts of dispersant.
[0008] Furthermore, the aromatic dianhydride is one of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride and bisphenol A dianhydride.
[0009] Furthermore, the aromatic diamine is one of diaminodiphenylmethane, 4,4'-diaminodiphenyl ether and 4,4'-diaminobiphenyl.
[0010] Furthermore, the dispersant is one of lignin sulfonate and sodium polyacrylate.
[0011] Furthermore, the modified carbon nanotubes are prepared by the following steps: Step 1, polyethylene glycol, succinic anhydride and N,N-dimethylformamide are added to a three-necked flask equipped with a magnetic stirrer, a condenser and a thermometer, nitrogen is introduced as a protective gas, and the mixture is heated until the temperature reaches 75°C, and the mixture is kept warm for 6 hours. After the reaction is completed, the mixture is washed with anhydrous ethanol for 3-4 times and dried in vacuo to obtain an intermediate product 1; Polyethylene glycol reacts with succinic anhydride to obtain intermediate 1; the specific reaction process is as follows: ; Step 2, add the intermediate product 1, n-decanol and N,N-dimethylformamide into a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, stir and mix, then add dibutyltin oxide and dicyclohexylcarbodiimide, heat until the system temperature reaches 80°C, keep the temperature for reaction for 6 hours, after the reaction is completed, remove part of the solvent by rotary evaporation, purify by column chromatography using a petroleum ether-ethyl acetate (5:2, v / v) elution system, and finally remove the residual eluent by reduced pressure distillation to obtain the intermediate product 2; Under the catalysis of dibutyltin oxide and dicyclohexylcarbodiimide, the hydroxyl group on the n-decanol and the carboxyl group on the intermediate product 1 undergo an esterification reaction, and the molar ratio of n-decanol to the intermediate product 1 is adjusted to be close to 1:1 (the intermediate product 1 is slightly excessive), ensuring that only one carboxyl group of the intermediate product 1 participates in the esterification; the intermediate product 2 is obtained; the specific reaction process is as follows: ; Step 3, the intermediate product 2, aminoethyl sulfide and N,N-dimethylformamide are added to a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, and after stirring and mixing, dicyclohexylcarbodiimide is added, and then the device is placed in a water bath pot, and reacted for 6 hours under a water bath condition of 50° C. After the reaction is completed, part of the solvent is removed by rotary evaporation, and column chromatography purification is performed using a petroleum ether-ethyl acetate (5:3, v / v) elution system, and finally the residual eluent is removed by reduced pressure distillation to obtain the intermediate product 3; Under the action of dicyclohexylcarbodiimide, the carboxyl group on the intermediate product 2 undergoes an amidation reaction with the amino group on the aminoethyl sulfide, and the molar ratio of the intermediate product 2 to the aminoethyl sulfide is adjusted to be close to 1:1 (slightly excessive aminoethyl sulfide), ensuring that only one amino group of the aminoethyl sulfide participates in the acylation reaction, thereby obtaining the intermediate product 3; the specific reaction process is as follows: ; Step 4, the carboxylated carbon nanotubes and N,N-dimethylformamide are mixed, and the carboxylated carbon nanotubes are evenly dispersed by ultrasonic treatment, and then the intermediate product 3 and dicyclohexylcarbodiimide are added, and magnetic stirring is performed for 2 hours, and then the mixture is kept in a water bath at 60° C. for 3 hours, and then the water bath is removed and magnetic stirring is performed at room temperature for 8 hours. After the reaction is completed, the mixture is filtered, and the filter residue is washed with anhydrous ethanol for multiple times, dried, and ground to obtain modified carbon nanotubes; Under the action of dicyclohexylcarbodiimide, -COOH on the surface of the carboxylated carbon nanotubes undergoes an amidation reaction with -NH2 on the intermediate product 3, and organic molecules are grafted onto the surface of the carbon nanotubes to obtain modified carbon nanotubes.
[0012] Furthermore, in step 1, the ratio of polyethylene glycol, succinic anhydride and N,N-dimethylformamide is 40g:21.3g:100mL.
[0013] Furthermore, in step 2, the ratio of the amount of the intermediate product 1, n-decanol, N,N-dimethylformamide, dibutyltin oxide, and dicyclohexylcarbodiimide is 61.2 g: 15.8 g: 150 mL: 0.4 g: 20.6 g.
[0014] Furthermore, in step 3, the ratio of the amount of intermediate product 2, aminoethyl sulfide, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 75.7 g:15.3 g:150 mL:20.6 g.
[0015] Furthermore, in step 4, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 3, and dicyclohexylcarbodiimide is 1 g:100 mL:17.6 g:6.3 g.
[0016] Carbon nanotubes are a material with extremely high thermal conductivity and excellent electrical conductivity. By grafting organic molecular chains on the surface of carbon nanotubes, the surface hydrophobicity of carbon nanotubes can be improved, thereby enhancing the compatibility of carbon nanotubes with polyimide matrix, thereby promoting the dispersion of carbon nanotubes and greatly reducing the agglomeration of carbon nanotubes. In addition, the grafted organic molecular chains contain a variety of functional groups, among which the polyethylene glycol structure contains a large number of ether bonds, which can improve the flexibility of the matrix. The introduced methylene units of the long carbon chain structure provide a high degree of rotational freedom, making the molecular chain soft, further enhancing the flexibility of the matrix, and the long carbon chain can also be interspersed in the macromolecular chain of the matrix, improving the stability of the modified carbon nanotubes. In addition, the introduction of thioether bonds makes the sulfur atom larger in size and wider in bond angle, and it is freer to rotate than the ether bond, further enhancing the flexibility of the matrix. Finally, the organic molecular chains are connected to the inorganic carbon nanotubes, making it difficult for organic molecules to migrate and seep out, further improving the stability of the organic molecular chains.
[0017] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps: The carbon nanotubes and the mixed acid were mixed, placed in an ice water bath at 2°C, and ultrasonically treated for 30 minutes, and then added to a three-necked flask equipped with a magnetic stirrer, a reflux condenser and a thermometer. Under magnetic stirring, the temperature was maintained at 80°C, and refluxed for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, added to ice water, and allowed to stand for precipitation, centrifuged for washing, and dried to obtain carboxylated carbon nanotubes; Furthermore, the mixed acid is obtained by mixing concentrated sulfuric acid with a mass fraction of 98% and concentrated nitric acid with a mass fraction of 65% in a volume ratio of 3:1.
[0018] Furthermore, the ratio of the carbon nanotubes to the mixed acid is 1 g:80 mL.
[0019] Beneficial effects of the present invention: The polyimide film prepared by the present invention has homemade modified carbon nanotubes added to the raw materials. Compared with ordinary carbon nanotubes, the modified carbon nanotubes have better compatibility with polyimide, are not easy to agglomerate, and have more fully exerted their performance, thereby greatly improving the antistatic and thermal conductivity of the polyimide film. Secondly, the organic molecular structure connected to the modified carbon nanotubes can also enhance the flexibility of the polyimide film and improve its mechanical properties. Therefore, the film prepared by the present invention has important application value in the technical field of polyimide films. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Embodiment 1 Preparation of modified carbon nanotubes: Step 1, add 40g polyethylene glycol (molecular weight 400), 21.3g succinic anhydride and 100mL N,N-dimethylformamide into a three-necked flask equipped with a magnetic stirrer, a condenser and a thermometer, introduce nitrogen as a protective gas, heat until the temperature reaches 75°C, keep the temperature for 6h, and after the reaction is completed, wash with anhydrous ethanol 3 times, and vacuum dry to obtain intermediate 1; Step 2, add 61.2g of intermediate product 1, 15.8g of n-decanol and 150mL of N,N-dimethylformamide into a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, stir and mix, then add 0.4g of dibutyltin oxide and 20.6g of dicyclohexylcarbodiimide, heat until the system temperature reaches 80°C, keep warm and react for 6h, after the reaction is completed, remove part of the solvent by rotary evaporation, and purify by column chromatography using a petroleum ether-ethyl acetate (5:2, v / v) elution system, and finally remove the residual eluent by reduced pressure distillation to obtain intermediate product 2; Step 3, add 75.7g of intermediate product 2, 15.3g of aminoethyl sulfide and 150mL of N,N-dimethylformamide into a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, stir and mix, add 20.6g of dicyclohexylcarbodiimide, and then place the device in a water bath pot, react for 6h under a water bath condition of 50°C. After the reaction is completed, remove part of the solvent by rotary evaporation, and purify by column chromatography using a petroleum ether-ethyl acetate (5:3, v / v) elution system, and finally remove the residual eluent by reduced pressure distillation to obtain intermediate product 3; Step 4: Mix 1 g of carboxylated carbon nanotubes and 100 mL of N,N-dimethylformamide, perform ultrasonic treatment to evenly disperse the carboxylated carbon nanotubes, then add 17.6 g of intermediate product 3 and 6.3 g of dicyclohexylcarbodiimide, stir magnetically for 2 h, and then keep warm in a water bath at 60 ° C for 3 h, remove the water bath and stir magnetically for 8 h at room temperature. After the reaction is completed, filter, wash the residue with anhydrous ethanol for several times, dry, and grind to obtain modified carbon nanotubes.
[0022] Embodiment 2 Preparation of modified carbon nanotubes: Step 1, add 80g polyethylene glycol (molecular weight 400), 42.6g succinic anhydride and 200mL N,N-dimethylformamide into a three-necked flask equipped with a magnetic stirrer, a condenser and a thermometer, introduce nitrogen as a protective gas, heat until the temperature reaches 75°C, keep the temperature for 6h, and after the reaction is completed, wash with anhydrous ethanol 4 times, and vacuum dry to obtain intermediate 1; Step 2, 122.4g of intermediate product 1, 31.6g of n-decanol and 300mL of N,N-dimethylformamide were added to a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, and after stirring and mixing, 0.8g of dibutyltin oxide and 41.2g of dicyclohexylcarbodiimide were added, and the mixture was heated until the system temperature reached 80°C, and the mixture was kept warm for 6h. After the reaction was completed, part of the solvent was removed by rotary evaporation, and column chromatography purification was performed using a petroleum ether-ethyl acetate (5:2, v / v) elution system, and the residual eluent was finally removed by reduced pressure distillation to obtain intermediate product 2; Step 3, 151.4 g of intermediate product 2, 30.6 g of aminoethyl sulfide and 300 mL of N,N-dimethylformamide were added to a three-necked round-bottom flask equipped with a magnetic stirrer, a condenser and a thermometer, and after stirring and mixing, 41.2 g of dicyclohexylcarbodiimide was added, and the device was placed in a water bath pot, and reacted for 6 hours under a water bath condition of 50°C. After the reaction was completed, part of the solvent was removed by rotary evaporation, and column chromatography purification was performed using a petroleum ether-ethyl acetate (5:3, v / v) elution system, and finally the residual eluent was removed by reduced pressure distillation to obtain an intermediate product 3; Step 4: Mix 2 g of carboxylated carbon nanotubes and 200 mL of N,N-dimethylformamide, perform ultrasonic treatment to evenly disperse the carboxylated carbon nanotubes, then add 35.2 g of intermediate product 3 and 12.6 g of dicyclohexylcarbodiimide, stir magnetically for 2 h, and then keep warm in a water bath at 60 ° C for 3 h, remove the water bath and stir magnetically for 8 h at room temperature. After the reaction is completed, filter, wash the residue with anhydrous ethanol for several times, dry, and grind to obtain modified carbon nanotubes.
[0023] Embodiment 3 A1. In a reaction kettle, add 51 g of pyromellitic anhydride, 43 g of diaminodiphenylmethane and 110 g of N,N-dimethylformamide, mix, introduce nitrogen as a protective gas, set the temperature to 20 ° C, stir and react for 20 minutes to obtain a polyamic acid solution; A2. The polyamic acid solution obtained in step A1 is mixed with 12 g of the modified carbon nanotubes obtained in Example 1 and 2 g of lignin sulfonate, and then subjected to ultrasonic treatment for 10 min, vacuum defoaming, cast film formation, thermal cyclization and bidirectional heat stretching treatment, and winding to obtain a high thermal conductive polyimide film.
[0024] Embodiment 4 A1. In a reaction kettle, add 57 g of biphenyltetracarboxylic acid dianhydride, 49 g of 4,4'-diaminobiphenyl and 140 g of N,N-dimethylformamide, mix, introduce nitrogen as protective gas, set the temperature to 30°C, stir and react for 30 minutes to obtain a polyamic acid solution; A2. The polyamic acid solution obtained in step A1 is mixed with 18 g of the modified carbon nanotubes obtained in Example 1 and 3 g of sodium polyacrylate, and then subjected to ultrasonic treatment for 30 min, vacuum defoaming, cast film, thermal cyclization and bidirectional thermal stretching treatment, and winding to obtain a high thermal conductive polyimide film.
[0025] Embodiment 5 A1. In a reaction kettle, add 63 g of biphenyltetracarboxylic acid dianhydride, 55 g of 4,4'-diaminobiphenyl and 160 g of N,N-dimethylformamide, introduce nitrogen as a protective gas, set the temperature to 30°C, stir and react for 30 minutes to obtain a polyamic acid solution; A2. The polyamic acid solution obtained in step A1 is mixed with 24 g of the modified carbon nanotubes obtained in Example 1 and 4 g of sodium polyacrylate, and ultrasonically treated for 30 min, and then vacuum defoamed, cast into a film, and then thermally cyclized and bidirectionally thermally stretched, and rolled up to obtain a high thermal conductive polyimide film.
[0026] Comparative Example 1 Ordinary carbon nanotubes of the same mass were used to replace the modified carbon nanotubes in Example 5, and the remaining steps were the same as in Example 5 to obtain a film.
[0027] Comparative Example 2 A commercially available polyimide film was used.
[0028] The following performance tests were performed on Examples 3, 4, 5, and Comparative Examples 1 and 2 according to different test standards: The resistivity is measured using the national standard GB / T 1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials" (the smaller the surface resistivity, the better the antistatic performance); Adopt ASTM-D696 standard to measure thermal conductivity and thermal expansion coefficient; The notched impact strength was measured using the ASTM-D6110 standard; The measured results are shown in the following table:
[0029] It can be seen from the above table that the polyimide film prepared in the embodiment of the present invention has higher antistatic, thermal conductivity and mechanical properties than the control example due to the addition of carbon nanotubes. Therefore, the film of the present invention has important application value in the field of polyimide film technology.
[0030] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0031] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A process for preparing a high thermal conductive polyimide film, characterized in that: The following steps are involved: A1. In a reaction kettle, add aromatic dianhydride, aromatic diamine and N,N-dimethylformamide, mix, introduce nitrogen, and stir to react at a set temperature to obtain a polyamic acid solution; A2, the polyamic acid solution obtained in step A1, the modified carbon nanotubes and the dispersant are ultrasonically treated, vacuum defoamed, cast into a film, and then thermally cyclized and bidirectionally heat-stretched, and rolled up to obtain a high thermal conductive polyimide film; Wherein, the modified carbon nanotubes are prepared by the following steps: Step 1, polyethylene glycol, succinic anhydride and N,N-dimethylformamide are added to a flask, nitrogen is introduced, and the temperature is heated until it reaches 75°C, and the reaction is kept warm for 6 hours. After the reaction is completed, the product is washed and vacuum dried to obtain an intermediate product 1; Step 2, add the intermediate product 1, n-decanol and N,N-dimethylformamide into a flask, stir and mix, then add dibutyltin oxide and dicyclohexylcarbodiimide, heat until the system temperature reaches 80°C, keep the temperature for 6 hours, after the reaction is completed, rotary evaporation, column chromatography purification, and reduced pressure distillation to obtain the intermediate product 2; Step 3, add intermediate product 2, aminoethyl sulfide and N,N-dimethylformamide into a flask, stir and mix, then add dicyclohexylcarbodiimide, react for 6 hours in a water bath at 50°C, after the reaction is completed, perform rotary evaporation, purify by column chromatography, and distill under reduced pressure to obtain intermediate product 3; Step 4: mix the carboxylated carbon nanotubes and N,N-dimethylformamide, and then add the intermediate product 3 and dicyclohexylcarbodiimide, and stir magnetically for 2 hours. Then, keep warm in a water bath at 60°C for 3 hours, and stir magnetically at room temperature for 8 hours. After the reaction is completed, filter, wash, dry, and grind to obtain modified carbon nanotubes.
2. A process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: In step 1, the ratio of polyethylene glycol, succinic anhydride and N,N-dimethylformamide is 40g:21.3g:100mL.
3. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: In step 2, the ratio of the amount of intermediate product 1, n-decanol, N,N-dimethylformamide, dibutyltin oxide, and dicyclohexylcarbodiimide is 61.2 g: 15.8 g: 150 mL: 0.4 g: 20.6 g.
4. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: In step 3, the ratio of the amount of intermediate product 2, aminoethyl sulfide, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 75.7 g:15.3 g:150 mL:20.6 g.
5. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: In step 4, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 3, and dicyclohexylcarbodiimide is 1 g:100 mL:17.6 g:6.3 g.
6. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 51-63 parts of aromatic dianhydride, 43-55 parts of aromatic diamine, 110-160 parts of N,N-dimethylformamide, 12-24 parts of modified carbon nanotubes, and 2-4 parts of dispersant.
7. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: The aromatic dianhydride is one of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride and bisphenol A dianhydride.
8. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: The aromatic diamine is one of diaminodiphenylmethane, 4,4'-diaminodiphenyl ether and 4,4'-diaminobiphenyl.
9. The process for preparing a high thermal conductive polyimide film according to claim 1, characterized in that: The dispersant is one of lignin sulfonate and sodium polyacrylate.
Citation Information
Patent Citations
Method for preparing polyester-ether elastomer / carbon nanotube composite material
CN102115530A
Carboxylated carbon nanotube / polyimides composite film and preparation method thereof
CN109929129A
Adhesive tape integrated sectional material with high wind pressure resistance
CN118812974A
Modified carbon nanotubes and their compatibility
US20130137822A1